Evaluating sorghums as green manure against root-knot nematodes. (August 2019) - Djian-Caporalino, Caroline; Mateille, Thierry; Bailly-Bechet, Marc; Marteu, Nathalie; Fazari, Ariane; Bautheac, Pierre; Raptopoulo, Alizée; Van Duong, Luan; Tavoillot, Johannes; Martiny, Bernard; Goillon, Claire; Castagnone-Sereno, Philippe
Abstract: Current restrictions on the use of chemical nematicides have led to an increase in root-knot nematode (RKN) damages in horticultural crops. The effects of two sorghums as summer cover crops, Sorghum sudanense sudangrass cv. 'Piper' or sudangrass hybrid [ S. bicolor x S. sudanense ] '270911', respectively with low and high dhurrin contents, were compared in their ability to suppress RKN in a vegetable production system. The use of both sorghums 'Piper' and '270911' as a green manure was found to be an effective strategy for decreasing RKN infestation in the soil, thereby protecting the subsequent planting of RKN susceptible crops (chard, lettuce or melon). Analytical experiments were further conducted in growth chamber and greenhouse pot experiments to investigate and compare the susceptibility of the sorghums and the factors affecting their efficacy for RKN management, in order to better explain the results obtained in the field trial. The two sorghums were poor hosts of RKN, acted as trap crops and as a biofumigant releasing hydrogen cyanide. Time of planting, time of biofumigation, and type of soil affected their efficacy for RKN management. For best RKN suppression, the sorghum cover crops need to be cultivated during one month or less and biofumigated for one month prior to crop planting. The trapping effect of both sorghums in clayey soil was less efficient than in sandy or sandy-loamy soils. Combining less than 30-days of sorghum culture and 10-days soil incorporation with solarization mulch was particularly efficient in suppressing nematodes. No effect relative to the sorghum type was detectable as long as they were used appropriately. Graphical abstract: Image 1 Highlights: Sorghum sudanense and sudangrass hybrids were poor hosts of root-knot nematodes. Sorghums acted as trap and as biofumigant plants releasing hydrogen cyanide. Low and high dhurrin sorghums were equally efficient to control Meloidogyne . Sorghums efficacy depended on time of cultivation and time of biofumigation. Soil types affected biofumigation efficacy for root-knot nematodes management.